A comparison of eye movement measures across reading efficiency quartile groups in elementary, middle, and high school students in the U.S. - Alexandra Spichtig; Jeffrey Pascoe; John Ferrara; Christian Vorstius (Bern Open Publishing, 2017)
This cross-sectional study examined eye movements during reading across grades in students with differing levels of reading efficiency. Eye-movement recordings were obtained while students in grades 2, 4, 6, 8, 10, and 12 silently read normed grade-leveled texts with demonstrated comprehension. Recordings from students in each reading rate quartile at each grade level were compared to characterize differences in reading rate, number of fixations, number of regressions, and fixation durations. Comparisons indicated that students in higher reading rate quartiles made fewer fixations and regressions per word, and had shorter fixation durations. These indices of greater efficiency were also characteristic of students in upper as compared to lower grades, with two exceptions: (a) between grades 6 and 8, fixations and regressions increased while reading rates stagnated and fixation durations continued to decline, and (b) beyond grade 6 there was relatively little growth in the reading efficiency of students in the lower two reading rate quartiles. These results suggest that declines in fixation duration across grades may in part reflect broader maturational processes, while higher fixation and regression rates may distinguish students who continue to struggle with word recognition during their high school years.